2005
DOI: 10.1038/nmat1353
|View full text |Cite
|
Sign up to set email alerts
|

Spin chirality on a two-dimensional frustrated lattice

Abstract: The collective behaviour of interacting magnetic moments can be strongly influenced by the topology of the underlying lattice. In geometrically frustrated spin systems, interesting chiral correlations may develop that are related to the spin arrangement on triangular plaquettes. We report a study of the spin chirality on a two-dimensional geometrically frustrated lattice. Our new chemical synthesis methods allow us to produce large single-crystal samples of KFe3(OH)6(SO4)2, an ideal Kagomé lattice antiferromag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
262
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(280 citation statements)
references
References 30 publications
14
262
2
1
Order By: Relevance
“…The low-temperature dependence of κ xy for the present model is plotted in Fig. 5(a) with the parameter values of KFe 3 (OH) 6 (SO 4 ) 2 [31]. At zero magnetic field there is no thermal Hall effect in accordance with the analysis of topological spin waves and edge modes discussed above.…”
Section: Arxiv:160804561v12 [Cond-matstr-el] 16 Jan 2017supporting
confidence: 79%
See 1 more Smart Citation
“…The low-temperature dependence of κ xy for the present model is plotted in Fig. 5(a) with the parameter values of KFe 3 (OH) 6 (SO 4 ) 2 [31]. At zero magnetic field there is no thermal Hall effect in accordance with the analysis of topological spin waves and edge modes discussed above.…”
Section: Arxiv:160804561v12 [Cond-matstr-el] 16 Jan 2017supporting
confidence: 79%
“…Hence, the DMI suppresses the QSL phase of frustrated kagomé antiferromagnets up to a critical value [30]. The syntheses of materials have shown that various experimentally accessible frustrated kagomé antiferromagnets show evidence of coplanar/noncollinear q = 0 LRO at specific temperatures [29][30][31][32][33][34] [36] are fragile in the presence of applied magnetic field or pressure and they show evidence of LRO [37,38]. However, the role of DMI and magnetic field in frustrated kagome magnets has not been investigated in the context of thermal Hall effect and topological spin excitations.…”
mentioning
confidence: 99%
“…This is in agreement with our finding that the thermal evolution of the single-crystal X-ray diffraction intensity of corresponding (0 2n+1 0) peaks is best fit with a critical exponent belonging to the 3D universality class. Although well-described by 2D theory in its low-pressure singlet phase, antiferromagnetic SCBO at high pressure supports the well-known Mermin-Wagner theorem (21,22) that long-range order can only survive fluctuations in three dimensions (23,24), and joins geometrically frustrated chiral magnets [25][26][27][28][29] in underscoring the importance of the DM interaction to the formation of exotic magnetic ground states.…”
Section: Significancementioning
confidence: 61%
“…The crystal structure of the -phase has been identified as rhombohedral c R3 in [28], tetragonal in [29], cubic mcm I / 4 m Pm3 in [30], monoclinic m P 1 2 or m C 2 in [31], and, recently, as orthorhombic Pbnm in [32]. The change of structure, loss of magnetic order and metallization of BiFeO 3 are also observed under pressure of [45][46][47][48][49][50][51][52][53][54][55] GPa at room temperature [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%